2021
DOI: 10.1002/marc.202100305
|View full text |Cite
|
Sign up to set email alerts
|

Novel Polymer‐Based Organic/c‐Si Monolithic Tandem Solar Cell: Enhanced Efficiency using Interlayer and Transparent Top Electrode Engineering

Abstract: Tandem solar cells which are electrically connected with various photoactive materials have the potential to solve the current challenges by exceeding the theoretically limited efficiency of single junction solar cells. Here the first monolithic organic/silicon tandem cell is reported based on a semitransparent polymer on a crystalline silicon (c-Si) substrate. Herein, experimental results are presented for four-terminal (4-T) and monolithic two-terminal (2-T) organic/c-Si tandem cells using organic cells with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…However, to achieve effective current matching with existing c-Si, emphasis should be placed on targeting short wavelengths more effectively. Simulation results suggest that efficiency of more than 20% is achievable through appropriate organic photoactive material and ICL engineering, surpassing the efficiency of existing single-junction OSCs …”
Section: Future Research Directions On Organic-based Hybrid Tandem So...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, to achieve effective current matching with existing c-Si, emphasis should be placed on targeting short wavelengths more effectively. Simulation results suggest that efficiency of more than 20% is achievable through appropriate organic photoactive material and ICL engineering, surpassing the efficiency of existing single-junction OSCs …”
Section: Future Research Directions On Organic-based Hybrid Tandem So...mentioning
confidence: 99%
“…Simulation results suggest that efficiency of more than 20% is achievable through appropriate organic photoactive material and ICL engineering, surpassing the efficiency of existing singlejunction OSCs. 188 Other Aspects for Organic Materials. For organic-based TSCs to progress further, considerations beyond performance improvement should also encompass aspects of organic materials.…”
Section: Organic-based Hybrid Tandem Solar Cellsmentioning
confidence: 99%
“…The following supporting information can be downloaded at: https://www.mdpi.com/article/10.3390/cryst14070584/s1, Figure S1: Absorption coefficients deduced from available experimental data for the bottom Si cell: (a) c-Si [54] and (b) a-Si layers [55]; Figure S2: Absorption spectrum of (a) PBDB-TCl:AITC absorber layer [34], (b) UV-vis absorption spectrum of PNDIT-F3N-Br layer [45], (c) Real, and (d) imaginary refractive index Refractive indices deduced from available experimental data for PEDOT:PSS layer [56]; Figure S3: (a) Illuminated J-V curves, and (b) EQE spectra of TSC and its cells, coupled using a tunnel junction; Figure S4: Efficiency over time for various tandem solar cell configurations from 2020 to 2024; Table S1: Definition of physical quantities used in Atlas device simulator; Table S2: Main parameters of various layers of organic solar cell [34,45,57]; Table S3: Defect parameters in OSC; Table S4: Main factors of various layers of thin Si cell [4,38,50,58]; Table S5: A state-of-the-art comparison between tandem cell metrics for a wide range of tandem systems [4,6,7,9,36,42,50,52,53,[59][60][61][62][63][64][65][66][67][68]…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…The optimized PCE exhibited 8.32% with VOC = 1.45 V. Despite the advantageous properties that may result from incorporating OSCs with silicon, there have been very few research efforts reported in this area. In [36], the authors presented the first fabricated organic/c-Si TSC, with record PCEs of 8.32% and 15.25% for 2-T and 4-T designs, respectively. The OSC utilized polymer-based materials, while the silicon bottom cell featured an n-type TOP-Con structure.…”
Section: Introductionmentioning
confidence: 99%
“…However, an important finding is that increasing the Si thickness is associated with an increase in PCE which poses a challenge for producing flexible tandems, in addition to the higher cost of Si compared to thin-film technology. In the context of organic/Si tandems, PCEs above 15% have been reported experimentally [58]. However, these tandems lack flexibility as the Si layer thickness is around 300 µm.…”
Section: Comparison Between Different Tandem Designsmentioning
confidence: 99%